PENGEMBANGAN BAHAN AJAR STATISTIKA ELEMENTER MENGGUNAKAN APLIKASI MINITAB - Meilisa, Mira; Kurnia, Lely (IAIN Batusangkar, 2018)
Amendment and development of education in Indonesia today requires various elements of education to participate in improving the quality of graduates to be able to compete in the global world. Indonesia was ranked 34th away from Singapore, Malaysia, Japan and Korea in the 20th position. This is because the educational institutions in Indonesia have not been able to produce graduates who are capable, superior, competeable with others. The educational tertiary education institution (LPTK) as one of the teacher producing institution has not been able to create prospective teacher who are ready to teach. The characteristic of the lecture process that is stated in Permenristek Dikti no. 44 of 2015 is interactive, holistic, integrative, scientific, contextual, thematic, effective, collaborative and student-centered. One way to realize this is to develop teaching materials that are used in applicable and communicative lectures. Based on the phenomenon, the researchers conducted research and development. In this study, researchers produce the elementary statistical teaching materials using the Minitab application by following Borg & Gall's research and development steps, namely (1) Carrying out information gathering (2) Designing (3) Develop the initial product form (4) Conduct pilot field trials. If can be concluded that the research on the development of statistical teaching materials that have produced valid products and can be used in lectures to develop student creativity. This development research should be continued in the next stage, namely the product effectiveness stage.